Business Sustainability Analysis of the Social Forestry Program in West Sumatra Province - Rachmina, Dwi; Herawati; Feryanto; Mahdi; Wibowo, Rulianda Purnomo; Azriani, Zednita (Universitas Muhammadiyah Yogyakarta, 2024)
The global community recognizes social forestry as a way to improve community welfare through sustainable forest programs. In Indonesia, this program aims to involve local communities in forest management, providing multiple benefits such as forest preservation, improved livelihoods, and poverty reduction. This study aims to analyze the sustainability of a social forestry program for both Community Forest (CF) and non-Community Forest (non-CF) schemes (Village Forests and Community Plantation Forests). The research was conducted in Sijunjung, Solok, Padang Pariaman Regencies, and Padang City, involving a sample of 33 CF participants and 65 non-CF participants selected through snowball sampling. The data were collected through direct interviews and focus group discussions (FGDs) at provincial and regency levels. The business sustainability assessment utilized multidimensional indicators (MDS) across three dimensions: economic, social, and institutional and analyzed using Rap_MForest. The findings revealed that social forestry program had a moderate level of sustainability in all dimensions; however, the social dimension showed lower sustainability, owing to limited community participation and ineffective empowerment of non-group members. The sustainability index of CF scheme was higher than the non-CF (VF and CPF). The CF model emerged as the more adaptable and comprehensive approach, promoting both environmental conservation and socioeconomic development. Therefore, prioritizing the institutional strengthening of VF and CPF became crucial. In addition, enhancing the active role and involvement of group members in the social forestry program within the social dimension was also essential. To enhance sustainability, efforts should be focused on strengthening mentoring and counseling programs for social forestry groups involved in state forest and community plantation initiatives.